Approximate solutions to BBM equations with bilinear control in a slowly varying medium - Wenxia Chen (Electronic Journal of Differential Equations, 2017)
This article concerns an approximate solution for the Benjamin-Bona-Mahony (BBM) equation with a bilinear control in slowly varying medium. By a sharp estimation of the error term, a suitable approximate solution for this equation is established.